Electrogenic amino acid transport in the intestine of sea bream (Sparus aurata): From functional characterization to physiological effects of Lysophospholipids in aquafeeds - Rocio Robles-Arozarena; Juan Antonio Martos-Sitcha; Laura Bermúdez; Waldo Nuez-Ortín; Juan Fuentes (Aquaculture Reports)
In response to sustainability concerns related to the origin of raw materials, aquaculture has emphasized the use of additives and enhancers to improve the intestinal absorption of proteins and amino acids. However, the tools available to have a good proxy for potential intestinal absorption and to expose positive or negative effects are scarce. The present study had a two-fold objective: we first aimed to characterize electrogenic essential amino acid transport in the intestine of the gilthead seabream ex-vivo. We also aimed to understand if dietary lysophospholipids (LPLs) had positive or detrimental effects when incorporated into commercial diets in gilthead seabream (Sparus aurata) juveniles. The ex-vivo characterization in Ussing chambers showed a region-dependent electrogenic amino acid transport in the sea bream intestine, being maxima in the mid intestine and with a strong luminal sodium- and pH-dependence. In vivo, the animals were divided into two groups: one was fed a control diet (10 % fishmeal inclusion), whereas the other group was fed with the control diet supplemented with 0.1 % LPL in coated form. The LPL-inclusion was without effects on fish growth in a short-term feeding trial, although there was a significant improvement of hepatosomatic and viscerosomatic indices. Interestingly, the intestine of fish fed the aquafeed with a 0.1 % LPL supplementation increased paracellular permeability as measured in the anterior intestine and enhanced electrogenic amino acid transport in the mid intestine. Our results strongly suggest that the full potential of LPL-inclusion benefits could be explored in sustainable diets, nearly devoid of fishmeal and/or in fish subjected to environmental stress.